Fermentation of a Pollen Substitute Diet with Beebread Microorganisms Increases Diet Consumption and Hemolymph Protein Levels of Honey Bees (Hymenoptera, Apidae) - Dias, Joyce Mayra Volpini Almeida; Morais, Michelle Manfrini; Francoy, Thiago Mauricio; Pereira, Rogério Aparecido; Turcatto, Aline Patricia; Jong, David de (Sociobiology, 2018)
Pollen substitute diets have become increasingly important for maintaining strong and healthy honey bee colonies. Palatability and nutritional value are key attributes of a good diet. Since beebread, which is pollen fermented by the bees, is the main food of the worker nurse bees that feed and care for the bee larvae, pollen substitutes should have similar attributes. In an attempt to simulate this natural food source, an inoculum prepared from beebread was used to ferment a pollen-substitute diet. Newly emerged bees were fed on the diets for seven days. They consumed significantly more fermented than unfermented diet. Hemolymph protein levels were significantly higher in bees that had been fed a fermented versus an unfermented diet, though still significantly lower than in bees fed on beebread. Vitellogenin (a key storage protein for honey bees) levels were also increased significantly in bees fed the fermented versus the non-fermented diet. Survival rates were higher for bees fed the fermented versus the non-fermented diet, though the difference was not significant. We conclude that fermentation by beebread-derived microorganisms can improve the acceptance and utility of an artificial protein diet for honey bees.